Prevention of Tuberculosis Transmission Through Mycobacterium Tuberculosis Detection in the Air - Juliasih, Ni Njoman; Koendhori, Eko Budi; Semita, I Nyoman (Kesmas, 2024)
Tuberculosis (TB) is a dangerous and highly contagious disease. Global cases have increased since, and Indonesia is one of the countries with the highest number of TB cases. This study aimed to prevent TB transmission by analyzing air contamination. Air samples were taken from three primary health cares (PHCs) in Surabaya City, East Java Province, Indonesia, and cultured in Mycobacterium Growth Indicator Tube (MGIT) media. Of the 108 air samples collected, 36 came from the waiting room, 36 from the examination room, and 36 from the laboratory room. As a result, the waiting room (50%), examination room (16.7%), and laboratory room (2.7%) were declared positive. In short, the air in the three PHCs contained mycobacterium tuberculosis. There is a need for room management to prevent TB transmission.